Research on Pressure-contact Technology of Power Terminals for the Design of High-integration IGBT Module - YUAN Yong; XIONG Hui; HUANG Nan; CHEN Yanping; XIN Li (Kongzhi Yu Xinxi Jishu)
It briefly introduced the package principle of pressure-contact IGBT devices. In order to achieve high-integration of IGBT module, the effect of pressure-contact technology on its impendence characteristic, parallel application and thermal performance was studied. A design scheme of press-contact IGBT device with elastic main power terminals was proposed and its key technology was described. Simulation and experimental results verified the efficiency of press-contact technology in IGBT module design and engineering application.